Aspek Hukum dalam Transaksi Jual Beli dengan Sistim Kredit dan Korelasinya dengan Perilaku Konsumsi Muslim - Miftakhul Huda (El-Faqih : Jurnal Pemikiran dan Hukum Islam, 2022)
The credit buying and selling system has an effect on both the seller and the buyer. There are those who feel that they are harmed, benefited, are equally harmed or are equally harmed. In this case, the seller and the buyer must both benefit, so that neither party feels disadvantaged. When both parties benefit from each other, the rural economy will run smoothly. The rural economy is currently able to develop, one of which is because of buying and selling on credit. So that the funds owned by the community are not solely used to buy or consume goods and services, but can also be used for other needs in order to get multiplied results, such as investment, and can also be used to save as future savings. However, there are two kinds of buying and selling credit, namely buying and selling credit that is allowed and buying and selling credit that is forbidden. Buying and selling credit that is allowed is buying and selling according to Islamic law, while buying and selling that is forbidden is buying and selling that is forbidden by Islamic law. Therefore, people, especially in rural areas, must be good at sorting out transactions that are included in the law of buying and selling credit and those that are prohibited from buying and selling credit, so as not to deviate from muamalah according to Islamic views.